2000
DOI: 10.1007/s11745-000-0658-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the addition products of α‐tocopherol with phosphatidylcholine‐peroxyl radicals by high‐performance liquid chromatography with chemiluminescent detection

Abstract: A chemiluminescence-based high-performance liquid chromatographic method was developed for the analysis of the addition products of alpha-tocopherol with phosphatidylcholine-peroxyl radicals (TOO-PC). The TOO-PC eluted from a reversed-phase column was reacted with a chemiluminescent reagent consisting of a Cypridina luciferin analog and a lipid-soluble iron chelate in acidic methanol at 50 degrees C, and the generated chemiluminescence was monitored. The detection limit for TOO-PC by this method was about 1 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In the free radical oxidation of 1,2-dilinoleoyl PC inhibited by a hydrophilic antioxidant, Trolox, in liposomes, the ratios of 9-hydroperoxy PC (9-OOH PC) to 13-hydroperoxy PC (13-OOH PC) were constant between 0.9 and 1.3 (22). Similar symmetrical distributions of hydroperoxide isomers were obtained when α-tocopherol was added to the liposomes (23)(24)(25)(26)(27). The mechanism of this phenomenon has been explained as an easy diffusion behavior of polar peroxyl radicals from the nonpolar lipid phase to the polar interface where peroxyl radicals are trapped or terminated by a water-soluble antioxidant (24).…”
Section: Discussionsupporting
confidence: 54%
“…In the free radical oxidation of 1,2-dilinoleoyl PC inhibited by a hydrophilic antioxidant, Trolox, in liposomes, the ratios of 9-hydroperoxy PC (9-OOH PC) to 13-hydroperoxy PC (13-OOH PC) were constant between 0.9 and 1.3 (22). Similar symmetrical distributions of hydroperoxide isomers were obtained when α-tocopherol was added to the liposomes (23)(24)(25)(26)(27). The mechanism of this phenomenon has been explained as an easy diffusion behavior of polar peroxyl radicals from the nonpolar lipid phase to the polar interface where peroxyl radicals are trapped or terminated by a water-soluble antioxidant (24).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, Miyashita et al (31) have demonstrated that oxygenation of methyl linoleate hydroperoxides yields dimers composed of octadecadienoate and octadecenoate moieties crosslinked through either ether or peroxy linkages across the 9-or 13-positions. Yamauchi et al (49) have shown the formation of α-tocopherol adducts with phosphatidylcholine peroxy radicals.…”
Section: Discussionmentioning
confidence: 99%
“…An HPLC-CL method was developed for the assay of α-tocopherol with phosphatidylcholine-peroxyl radicals (TOO-PC) using 2-methyl-6-phenyl-3,7-dihydroimidazo [1,2-a]pyrazin-3-one, a Cypridina luciferin analog, as the sensitive amplifier of CL produced by the iron-induced decomposition of TOO-PC under acidic conditions [109].…”
Section: Miscellaneousmentioning
confidence: 99%